New Horizons: World Summit on the Information Society (WSIS) - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 2004)
The first of two phases of the World Summit on the Information Society (WSIS) took place in Geneva from 10 to 12 December 2003 and was hosted by the Government of Switzerland.